Anesthesia for Cesarean Section - Capogna, Giorgio (Springer International Publishing : Imprint: Springer, 2017)
This book examines every aspect of anesthesia in patients undergoing cesarean section. Anesthetic and surgical techniques are clearly described, with detailed guidance on indications and contraindications and identification of potential complications. Practical information is provided on postoperative analgesia, postoperative course and nursing, the significance of cesarean section for breastfeeding, and the occurrence of long-term problems and chronic pain after cesarean section. Other topics to be addressed include the history and epidemiology of cesarean delivery, effects on the fetus and neonate, ethical issues, the humanization of childbirth, and maternal expectations and satisfaction. While many books are available on obstetric anesthesia, none is exclusively devoted to cesarean section although it is one of the most frequently performed surgeries. Anesthesia for Cesarean Section will be appreciated by all anesthesiologists and will be a useful source of information for obstetricians, gynecologists, midwives, nurses, medical students, and trainees.